Leucyl-tRNA synthetase from Thermus thermophilus. Purification and some properties of the crystallizing enzyme - Yaremchuk, A.D.; Gudzera, O.I.; Egorova, S.P.; Rozhko, D.I.; Kriklivy, I.A.; Tukalo, M.A. (Біополімери і клітина, 2001)
Leucyl-tRNA synthetase from Thermus thermophilus (LeuRSTT) was purified to homogeneity using a five-step purification procedure. The enzyme was characterized and crystallized. Molecular mass determinations of the native and denatured proteins indicate monomeric structure of LeuRSTT with the molecular mass of about 101 kDa. The protein obtained is remarkably thermostable and retains 97 % of its initial aminoacylation activity after 1 hour of incubation at 88 °C. Crystals of LeuRSTT were obtained from ammonium sulfate solution by the vapour diffusion techniques. The crystals quality was improved by crystallization from the precipitate.